Development of an outcome measurement system for service planning for children and youth with special needs. Issue 5 (30th July 2012) - Kertoy, M. K.; Russell, D. J.; Rosenbaum, P.; Jaffer, S.; Law, M.; McCauley, D.; Gorter, J. W.
Abstract Aim This study described the process used in developing an outcome measurement framework for system planning to improve services for children and youth with special needs and their families in a Canadian province. The study reports the results of several parent‐completed measures, which would be useful in service planning as well as the acceptability and utility of these measures for use by families and service centres. Methods/results Development of a theoretical framework, consultation with key stakeholders, testing the utility of selected outcome measures and initial dissemination of results were critical elements in the successful development of an outcome system. Consultation with stakeholders confirmed use of the International Classification of Functioning, Disability and Health and the child‐within‐family‐within community model as theoretical frameworks while building valuable partnerships and identifying potential barriers to implementation. Pilot testing showed three outcome measures were feasible for families to complete and the measures provided information about services for children that was valuable to families as well as service providers. Gaps in service delivery were identified and the need for better communication between service providers and communities to facilitate integrated services was highlighted. Conclusion The findings from this study can be used to implement an outcome measurement system for children with special needs and may serve as a resource for international researchers who are working to develop valid tools as well as outcome systems that are useful for system planning.